Penatalaksanaan Fisioterapi Pada Bronkitis Kronis Di Balai Besar Kesehatan Paru Masyarakat Surakarta - Riyanto, Slamet, Isnaini Herawati, S.Fis, S.Pd, M.Sc (2017)
Background: Bronchitis Chronic is a form of development of chronic obstructive pulmonary disease (COPD) or airway abnormalities in which it is characterized by excessive mucus production in tracheobroncus as well as chronic coughs approximately three months in a year or for two consecutive years. Symptoms that often arise are shortness of breath, cough, and excessive production of sputum. In overcoming these problems the physiotherapy modalities used are infra red and Forsed Expiration Technique (FET). purpose: To investigate out whether infra red and Forced Expiration Technique (FET) can facilitate sputum expenditure and reduce shortness of breath in patients with chronic bronchitis. Results: After 4 times of interfering therapy, it was seen that at T0 there was a lot of sputum buildup, the next day after the interaction of therapy on T4 is no longer heard of sputum accumulation on patient's airway. At degrees congested with using borg scale Visible on T0 has infra red value 4, which means shortness of weight and on T4 has decreased degrees suffocation significant enough that has a value of borg scale 2 which means shortness of lightness. Conclusion: The management of physiotherapy in cases of chronic bronchitis results in the accumulation of sputum accumulation on the airway and decreased degrees with Borg scale,